Metastatic tuberculous abscess in an immunocompetent individual - Trishna Vaishali Muthurathinam; Sheron Christin Armel; Nithiyaa Pavadai; Prince Solomon (Journal of Current Research in Scientific Medicine)
Metastatic tuberculous abscess is a very rare endogenous tuberculosis that presents as painless nodules in the trunk and extremities which later ulcerates and is commonly seen in immunocompromised adults and malnourished children. A 17-year-old girl presented with an ulcer on her right lower back for 1 week which initially started as a painless nodule and then ruptured spontaneously. On examination, an indurated plaque of size 5 cm × 3 cm with multiple small ulcers with pus discharge was present on the right lumbar region. Three erythematous soft tender swellings of size measuring approximately 8*5 cm over the right elbow, 3*3 cm over the dorsum of the left hand and 4*3 cm over the back near the midline was present. Acid-fast bacilli were demonstrated on Ziehl–Neelsen staining. GeneXpert was positive. Magnetic resonance imaging of the spine showed multiple cold abscesses in D5-L3 and lymph nodes. Histology showed multiple well-to-ill-defined granulomas and Langhans giant cells. She was started with antitubercular therapy and showed significant improvement. We report this case since metastatic tuberculous abscess is very rare, and also, there is multifocal involvement including spine, pulmonary, and lymphatics in an immunocompetent individual.